2012
DOI: 10.1093/intqhc/mzs014
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety and medical errors: knowledge, attitudes and behavior among Italian hospital physicians

Abstract: The results from our study highlight that greater efforts are needed to facilitate the translation of positive attitudes towards patient safety into appropriate practices that have proven to be effective in the reduction of medical errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 28 publications
3
35
1
6
Order By: Relevance
“…They pointed out that qualification in medical education should be upgraded and that branching in nursing education is very important. Understanding what are the main factors that cause medical errors and developing effective practices to overcome them is essential in ensuring patient safety (28).…”
Section: Discussionmentioning
confidence: 99%
“…They pointed out that qualification in medical education should be upgraded and that branching in nursing education is very important. Understanding what are the main factors that cause medical errors and developing effective practices to overcome them is essential in ensuring patient safety (28).…”
Section: Discussionmentioning
confidence: 99%
“…Vincent JL et al in 1998 [25] who conducted a research on medical error disclosure among physicians in the European Union region, found that 32% of doctors would disclose a medical error and 63% would play down the incident and blame it on something else. In an Italian national study conducted by Domenico Flotta et al in 2012 [26] reported that 90.2% of doctors felt that they should not conceal medical errors that occur while providing clinical management.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing unnecessary follow‐ups releases capacity for the treatment of new patient referrals. Furthermore, higher reporting of clinical and nonclinical errors can lead to improved quality and lower costs . While some patient safety–related incidents are inevitable, it is generally accepted that many are preventable.…”
Section: Datamentioning
confidence: 99%